Touristification - Mendes, Luís (2022)
Touristification refers to the impact of mass tourism on the commercial and social fabric of neighbourhoods, causing services, facilities and shops to be oriented towards and conceived of in reference to the tourist rather than the resident. It is the process of making an urban, rural or natural space suitable for tourists. An increase of the number of tourists and tourism businesses in a given territory magnifies the impact created. The term has been used in conjunction (or interchangeably) with over-tourism to designate the overcrowding and excess of tourism, as well as its impacts on the local population and on the tourism industry itself (Renau, 2018)